2004
DOI: 10.1158/1078-0432.ccr-0811-03
|View full text |Cite
|
Sign up to set email alerts
|

Role of Estrogen Receptor in the Regulation of Ecto-5′-Nucleotidase and Adenosine in Breast Cancer

Abstract: Purpose:The purpose is to understand the expression of ecto-5-nucleotidase (eN), an adenosine producing enzyme with potential roles in angiogenesis, growth, and immunosuppression, in estrogen receptor (ER)-negative and -positive breast cancer.Experimental Design: We investigated the regulation of eN expression at the mRNA and protein levels by ␣ in a panel of breast cancer cell lines that differ in ER status and invasive and metastatic potential. We also determined rates of adenosine formation in cells with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 60 publications
4
87
1
2
Order By: Relevance
“…In breast-cancer cells, CD73 expression has been shown to be regulated by estrogen receptors (ER), whereby loss of ER significantly enhances CD73 expression (17). Both tumor and host CD73 co-operatively protect tumors from incoming antitumor T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In breast-cancer cells, CD73 expression has been shown to be regulated by estrogen receptors (ER), whereby loss of ER significantly enhances CD73 expression (17). Both tumor and host CD73 co-operatively protect tumors from incoming antitumor T cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, he said there is evidence for CD73 expression in primary human tumors and that other researchers have shown a correlation between CD73 expression and lack of estrogen receptor in primary breast tumors. 3 Zijlstra said additional studies might be needed to confirm the antibody's mechanism of action in reducing primary tumor growth. He said it wasn't clear whether the anti-CD73 antibody was working by shutting off adenosine production or through antibody-dependent cellular cytotoxicity (ADCC).…”
Section: Analysis Targets and Mechanismsmentioning
confidence: 99%
“…He added that the team's results suggest anti-CD73 therapies might be most beneficial in patients with advanced metastatic cancer. Emma Shtivelman, director of cancer research at Bionovo Inc., noted that CD73 expression has been correlated to breast cancer cell lines that do not express estrogen receptor, 3 which is one of the three missing receptors in triple-negative breast cancers.…”
mentioning
confidence: 99%
“…Results demonstrated that ATP hydrolysis was enhanced and ADP hydrolysis was reduced as a function of tamoxifen use, while AMP hydrolysis was unchanged [4]. The expression of ecto-5'-nucleotidase is negatively regulated by the estrogen receptor (ER) in breast cancer cells; as ER expression decreases, ecto-5'-nucleotidase increases, leading to increased generation of adenosine, which may be related to breast cancer progression [123].…”
Section: Ectonucleotidase Activity In Cancermentioning
confidence: 99%
“…However, purinergic signaling may also have a profound impact on other more protracted reactions observed in several chronic inflammatory states, such as cell proliferation, differentiation, and apoptosis [13,20,37,123].…”
Section: Immunomodulation and Cell-cell Interactionsmentioning
confidence: 99%